2010
DOI: 10.1080/13607860903191382
|View full text |Cite
|
Sign up to set email alerts
|

The long-term impact of childhood abuse on internalizing disorders among older adults: The moderating role of self-esteem

Abstract: The negative effects of childhood abuse persist for many years, even into older adulthood. However, contrary to the findings in younger adults, self-esteem was not correlated with childhood abuse in older adults. Moreover, childhood abuse only had a negative effect on those who had low self-esteem. It may be through the process of lifespan development that some abused individuals come to separate out the effects of abuse from their self-concept.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
35
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 63 publications
5
35
0
1
Order By: Relevance
“…In a study of 2402 low-income women aged 19 74 years in the US, Hill et al found that the effect of sexual coercion before age 18 years on psychological distress is partially mediated by instrumental support and selfesteem (110). In a study of older adults (50 years and older), Sachs-Ericsson et al found that self-esteem moderates but does not mediate the relationship between childhood abuse (physical, emotional and sexual abuse) and internalizing disorders (111). Studies have also reported associations between low self-esteem and poor QoL or well-being in general adolescent populations (112) and in adolescent and adult populations with psychiatric problems (113)(114)(115)).…”
Section: Self-esteemmentioning
confidence: 93%
“…In a study of 2402 low-income women aged 19 74 years in the US, Hill et al found that the effect of sexual coercion before age 18 years on psychological distress is partially mediated by instrumental support and selfesteem (110). In a study of older adults (50 years and older), Sachs-Ericsson et al found that self-esteem moderates but does not mediate the relationship between childhood abuse (physical, emotional and sexual abuse) and internalizing disorders (111). Studies have also reported associations between low self-esteem and poor QoL or well-being in general adolescent populations (112) and in adolescent and adult populations with psychiatric problems (113)(114)(115)).…”
Section: Self-esteemmentioning
confidence: 93%
“…Afifi et al (2008) found that the estimated attributable fractions for psychiatric disorders related to having experienced any ACE (childhood sexual or physical abuse, domestic violence) ranged from 22% to 32% among women and 20% to 24% among men. A particularly strong link has been identified between childhood physical, sexual abuse and neglect and the mood and anxiety disorders (Heim et al, 2008(Heim et al, , 2010Liu et al, 2012;Sachs-Ericsson et al, 2010). For example, researchers found that people who were verbally abused had 1.6 times as many symptoms of depression and anxiety as those who had not been verbally abused and were twice as likely to have suffered a mood or anxiety disorder over their lifetime (Sachs-Ericsson, Verona, Joiner, & Preacher, 2006).…”
Section: Gene-environmentmentioning
confidence: 96%
“…From evidence across numerous studies, researchers have concluded that the effects of ACEs on physical and mental health conditions persist throughout the life course (Draper et al., ; Sachs‐Ericsson et al., ; Sachs‐Ericsson, Medley, Kendall–Tackett, & Taylor, ; Sachs‐Ericsson, Rushing, Stanley, & Sheffler, ). For example, in a large population‐based cohort study of middle‐aged men and women, researchers found that retrospective reports of childhood physical abuse were associated with worse physical health decades after the abuse (Springer, Sheridan, Kuo, & Carnes, ).…”
Section: Definition Of Childhood Abuse and Acesmentioning
confidence: 99%